153 Characteristics of Animal Science Graduate Students Associated with Their Professional Interest in Statistics and Career Path - Serão, Nick V (J Anim Sci, 2021)
Statistical training is a major component in the education of animal science graduate students (ASGS). Although most graduate courses in animal science require ASGS to take credits in statistics courses, ASGS differ on their educational and professional interest in statistics. Thus, the aim of this study was to identify associations between the overall graduate and statistical training of ASGS with the statistical interest related to their professional career path. Data from a nationwide statistical training survey was used and included information on 381 ASGS from 42 universities. Analyses focused on identifying overall graduate and statistical training factors associated with ASGS’s answers to the following questions: “Gives statistical advices to lab peers” (No/Yes), “Gives statistical advices to others outside the lab” (No/Yes), “Desired career path after graduation” (Academia/Industry/Other), and “Desire to be involved in statistical analysis in desired career path” (No/Somewhat/Yes). Data were analyzed using logistic regression model including 11 fixed effects, such as degree being pursued (MS/PhD), years of graduate education (covariate), previous professional experience (No/Yes), preferred stats software (SAS/R/SAS and R/Other), etc. There were significant associations (P < 0.05) for all four analyses. ASGS were more likely to give statistical advice to lab peers as they had more years of graduate education [odds-ratio (OR)=1.33], had additional training in statistics (OR=1.92), and had analyzed their own dataset (OR=4.46). ASGS with and without previous professional experience had greater desire to go to industry (OR=1.3) and academia (OR=1.23), respectively. ASGS interested in being involved in statistics in their future career had greater years of graduate education (OR=1.31) and credits in stats courses (OR=1.31), had previously completed a graduate degree (OR=1.49), had previous research experience (OR=1.5), and had additional training in statistics (OR=1.54). These results indicate that a variety of experiences prior to and during graduate ASGS education are associated with their interest in statistics.